2020
DOI: 10.1038/s41598-020-77906-1
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated temperature, but not decreased pH, impairs reproduction in a temperate fish

Abstract: Fish reproductive success is linked to the ability of couples to mate and produce clutches that successfully hatch. Environmental stressors like high temperature and low pH can jeopardize this energetically costly process. In this study, exposure to high temperature and low pH was tested on a marine temperate species, Gobiusculus flavescens, to evaluate effects on reproductive performance. Breeding pairs were assigned to different temperatures (+ 0 °C, + 3 °C relative to in situ temperature) and pH levels (8.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Previous OA studies in laboratory and natural conditions have considered only a small number of behavioural activities at the same time (Milazzo et al, 2016;Sundin et al, 2017;Lopes et al, 2020), with this likely underestimating the potential energy/time reallocation towards other keys behaviours. Aquaria experiments showed no differences in some activities such as fanning, courtship and nest building in the three-spined stickleback Gasterosteus aculeatus (Sundin et al, 2017) and in the two-spotted goby Gobiusculus flavescens (Lopes et al, 2020). Similarly, no effects of elevated CO2 on the time spent in courtship behaviour and on the number of chasing events were observed for the ocellated wrasse at the Vulcano CO2 seep site (Milazzo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous OA studies in laboratory and natural conditions have considered only a small number of behavioural activities at the same time (Milazzo et al, 2016;Sundin et al, 2017;Lopes et al, 2020), with this likely underestimating the potential energy/time reallocation towards other keys behaviours. Aquaria experiments showed no differences in some activities such as fanning, courtship and nest building in the three-spined stickleback Gasterosteus aculeatus (Sundin et al, 2017) and in the two-spotted goby Gobiusculus flavescens (Lopes et al, 2020). Similarly, no effects of elevated CO2 on the time spent in courtship behaviour and on the number of chasing events were observed for the ocellated wrasse at the Vulcano CO2 seep site (Milazzo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a laboratory experiment, Sundin et al (2017) did not detect any CO2 effect on the nest building activity, courtship and fanning of the threespined stickleback Gasterosteus aculeatus (Linnaeus 1758). Similarly, no CO2 effects were detected on the time males of two-spotted goby Gobiusculus flavescens (Fabricius, 1779) spent on differential parental care behaviours, with this male investment being mostly affected by increased temperature in a 2×2 (CO2 × T) factorial experiment carried out in lab conditions (Lopes et al, 2020). In the first study carried out in the wild so far, no differences in many mating behaviours were detected, but the number of pair spawning events with females by the nesting male ocellated wrasse Symphodus ocellatus was reduced by almost two thirds in areas at high CO2 levels near volcanic seeps (Milazzo et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…For ectotherms, temperature is a key environmental factor that influences several fundamental processes such as behaviour [1,2], metabolism [3,4], reproduction [5,6], growth, and development [7,8]. In a world of rapid warming, with ocean temperature projected to increase up to 4 • C until the end of the century [9,10], it is imperative to understand the overall consequences to marine life.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature is a crucial ecological component that affects fish life [ 1 ]. Various studies have shown that fluctuations in water temperature impact fish development, sexual reproduction, mobility, behavior, and metabolism [ 2 , 3 , 4 , 5 , 6 ]. Typically, fish can adjust to the encompassing temperature around them and keep up homeostasis by rebalancing their behavioral, physiological, biochemical, and molecular processes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%